Development of a flowchart of the processes of a risk-based MRO system applied to mining enterprises - Chernyh V.G.; Otrokov A.V.; Grinko D.A.; Grinko A.A.; Mironova A.O.; Bogatyrev A.R. (Горное оборудование и электромеханика, 2025)
This article discusses the key aspects of developing process flowcharts for risk-based maintenance and repair (MRO) systems. The main attention is paid to the study of the methodology for creating such schemes that take into account various types of risks associated with the operation of equipment and its maintenance. The paper presents the results of an analysis of existing approaches to risk management in MRO systems, as well as recommendations for optimizing processes based on identified risks. The authors propose a structured approach to the development of flowcharts, which includes the identification of critical control points, the choice of optimal methods for monitoring the condition of equipment and the development of corrective action plans in case of deviations from the norm. Examples of the application of the proposed methodology in real mining facilities are considered, which makes it possible to assess its effectiveness and practical significance. The main stages of creating such a scheme are described, starting with the analysis of existing processes and the identification of key risks associated with the operation of equipment. Special attention is paid to the methods of risk identification and assessment, as well as their impact on the reliability and safety of production systems. The principles of building flowcharts are described, which make it possible to integrate risk management methods into the daily activities of enterprises. Attention is paid to the practical aspects of applying the developed solutions in real-world operating conditions of industrial equipment.